A Risk Analysis of Occupational Safety and Health (OSH) Using the Hazard And Operability Study (HAZOP) Method for the Semani Drainage Project (Sentosa-Remaja-A. Yani): Rekayasa - Rusli, Rusli; Zulkarnain, Isnaini; Ekandari, Yeyen (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2024)
The purpose of this research is to analyze the risk of accidents in the construction project of drainage in Semani (Sentosa-Remaja-A. Yani) with the aim of assessing the level of accident risk that occurs. Occupational Safety and Health is an obligation mandated by the Labor Law and the Minister of Manpower Regulation, so that the risk of accidents can be minimized. In the implementation of the drainage project in Semani (Sentosa-Remaja-A. Yani), the Occupational Safety and Health System (K3) has been applied properly, but accidents often result from the negligence of the workers themselves. Therefore, an appropriate approach is needed to identify accident risks. Hazard and Operability Study (HAZOP) is a method that can be applied to identify and analyze the risks of work accidents. The research results show that high-risk conditions account for 32%, medium-risk for 54%, and low-risk for 14%, so improvement recommendations are more focused on high and medium-risk conditions